2018
DOI: 10.1111/are.13654
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterial community in different parts of the gut of sea cucumber (Apostichopus Japonicus ) and its variation during gut regeneration

Abstract: Bacterial community plays an important role in keeping the health status of the host. A study on the characteristics of gut bacterial community of sea cucumber (Apostichopus japonicus) not only helps improve the current aquaculture model, but promotes healthy and rapid development of the aquaculture industry as well. Therefore, taking pond‐cultured sea cucumber (A. japonicus) as the studying object, the metagenomic and 16S rRNA sequencing technology were used in this study to explore the characteristics of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 35 publications
(49 reference statements)
6
34
1
Order By: Relevance
“…In this study, high-throughput sequencing results suggested that bacterial community structures in the intestine of A. japonicus showed significant differences in different regeneration stages. This result is consistent with a previous study (Wang et al, 2018). In the early stage (10 days), a sharp decline in the species richness and diversity of intestinal bacteria was observed, suggesting that the absence of an intestine led to the development of extensive and varied bacterial diversity in the intestine of A. japonicus .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, high-throughput sequencing results suggested that bacterial community structures in the intestine of A. japonicus showed significant differences in different regeneration stages. This result is consistent with a previous study (Wang et al, 2018). In the early stage (10 days), a sharp decline in the species richness and diversity of intestinal bacteria was observed, suggesting that the absence of an intestine led to the development of extensive and varied bacterial diversity in the intestine of A. japonicus .…”
Section: Discussionsupporting
confidence: 94%
“…The intestinal bacterial community structures also changed at the phylum and class levels, and particularly at the genus level in the early stage, and then varied significantly in the later stages (14–18 days). Notably, the community composition recovered to a certain extent at the end of regeneration and was similar to the control (Figure 2 and Supplementary Figure 2), which is consistent with a previous report that bacterial community structure in the intestine of A. japonicus tended to be stable after 21 days of regeneration (Wang et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, molecular fingerprinting technology revealed that bacterial diversity in the canine colon and rectum was significantly higher than the duodenum and jejunum (Suchodolski, Ruaux, Steiner, Fetz, & Williams, 2005). Moreover, bacterial communities in the midgut and hindgut of sea cucumbers had a significantly higher richness and diversity when compared with the foregut (Wang et al, 2018). Taken together, the posterior compartment of the intestinal tract could be more suitable for microbial colonization across diverse animal species.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies are beginning to shed light on the gut microbiomes found in various echinoderm taxa, among them several deposit-feeding sea cucumber ( Gao et al, 2014 ; Yamazaki et al, 2016 ; Wang et al, 2018 ; Pagán-Jiménez et al, 2019 ; Weigel, 2020 ) and sea urchin species ( Thorsen, 1999 ; Thorsen et al, 2003 ; da Silva et al, 2006 ; Schwob et al, 2020 ). However, most of these analyses focus on microbial organisms found in the main digestive tract, while the present study provides data permitting a comparison between the microbiomes found inside the main gut compartments and a specialized digestive tract derivative.…”
Section: Discussionmentioning
confidence: 99%